2002
DOI: 10.1056/nejmoa013410
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Nocturnal Blood Pressure and Progression to Microalbuminuria in Type 1 Diabetes

Abstract: In persons with type 1 diabetes, an increase in systolic blood pressure during sleep precedes the development of microalbuminuria. In those whose blood pressure during sleep decreases normally, the progression from normal albumin excretion to microalbuminuria appears to be less likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
407
6
27

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(471 citation statements)
references
References 36 publications
25
407
6
27
Order By: Relevance
“…It is possible that the increase in blood pressure in patients progressing to overt nephropathy is evident only in close temporal relationship with the increase in AER, and thus may have been missed in the 7-year follow-up interval. It has also been observed that an increase in AER values in Type 1 diabetic subjects may be heralded by an abnormal pattern of night-time blood pressure [39]. We cannot, therefore, rule out that differences in blood pressure at baseline may not have been detectable with a single office measurement, but could have been found if 24-h blood pressure measurements had been performed [40,41].…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that the increase in blood pressure in patients progressing to overt nephropathy is evident only in close temporal relationship with the increase in AER, and thus may have been missed in the 7-year follow-up interval. It has also been observed that an increase in AER values in Type 1 diabetic subjects may be heralded by an abnormal pattern of night-time blood pressure [39]. We cannot, therefore, rule out that differences in blood pressure at baseline may not have been detectable with a single office measurement, but could have been found if 24-h blood pressure measurements had been performed [40,41].…”
Section: Discussionmentioning
confidence: 92%
“…2,3 A series of reports dealing with diabetic patients have also shown a close correlation between ambulatory BP and diabetic complications. 4,5 Evidences are available for the entire cardiorenal continuum of diabetic damage from the prediction of microalbuminuria by early changes in nocturnal BP in type 1 patients 6 to the effect of a riser pattern on mortality in patients with type 2 diabetes. 7 Nevertheless, information about the ABPM characteristics of large cohorts of diabetic hypertensives attending primary care centers is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…At present, no studies on the long-term predictive value of ambulatory PP for nephropathy progression in patients with type 2 diabetes have been published. Impaired nocturnal BP decline ('non-dipping') is another BP abnormality that has been associated with micro- [1,[10][11][12][13][14][15][16][17] and macrovascular [1,18] complications in type 1 and type 2 diabetic patients. In a recently published 3 year follow-up study in elderly patients with type 2 diabetes [19], patients with a reversed diurnal BP rhythm (nocturnal BP 'risers') had an increased risk of nephropathy progression compared with those who had a normal reduction in BP during the night ('dippers').…”
Section: Introductionmentioning
confidence: 99%